The Shanghai Effect: Do Exports to China Affect Labor Practices in Africa?. (January 2017) - Adolph, Christopher; Quince, Vanessa; Prakash, Aseem
Highlights: Export destinations' labor standards affect African countries' own labor standards. On average, increasing African exports to China slightly lowers labor standards in Africa. But country-specific "Shanghai Effects" vary with the composition of export destinations replaced by China. Where China exports replace exports to high standard countries such as the EU, the Shanghai Effect is much larger. Where China exports replace exports to low standard countries, the Shanghai Effect disappears. Summary: To investigate whether Africa's exports to China influence labor practices in Africa, we reconsider the debate over trade's influence on regulatory standards in exporting countries. The first generation of trade–regulation scholars asked whether high levels of exports influenced regulatory standards of exporting countries, with inconclusive results. The second generation of scholarship focused not on how much a country exported but to whom it exported, identifying a "California Effect" by which firms and consumers in (mostly developed) importing countries projected their high regulatory standards on less developed export partners. Structural change—especially the rise of China as a major importer—poses a challenge to these optimistic findings. Drawing on insights from the analysis of compositional data, this paper introduces a third generation of trade–regulation research, which suggests examining not only with whom a country trades, but also how the composition of markets in a country's export basket reshuffles over time. Specifically, we explore the possibility of a "Shanghai Effect" whereby African countries begin to reflect the lower labor standards of China, which has emerged as a major destination for their exports. We show that when a country increases exports to China, the net effect on domestic labor standards depends critically on the labor practices of other export destinations compositionally displaced by China exports. Our analysis of a panel of 49 African countries for the period 1985–2010 produces a small continent-wide estimate of China's negative influence on African labor practices. In-sample simulation at the country level uncovers a moderate Shanghai Effect for a handful of countries only.